Integrasi Sistem Transportasi Publik sebagai Penunjang Sektor Pariwisata Badung Selatan - Putri, Dewa Ayu Putu Adhiya Garini; Putrawan, Ni Wayan Karishma Vidya Poedja (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
Badung Regency is currently one of the tourism areas that generates travel, this certainly results in a high economic turnover which has an impact on increasing the number of private vehicles and services to and from the area. This study aims to determine efforts to integrate public transportation systems so that it is expected to improve accessibility and support tourism in South Badung. The research location was carried out in the South Badung area targeting Metro Dewata bus public transportation users.This research uses quantitative methods with the approach of perceptions and preferences of public transportation users who are more concerned with quality service analysis and importance-performance analysis. Based on the results of the study, it is known that respondents are still dissatisfied with the quality of service of the current integration of the public transportation system as evidenced by the servqual value of all integration still less than 0 and the level of conformity which is still below 100% so that it needs to be improved and adjusted again the quality of service. This can be done by developing a public transportation system integration strategy. The variable type of integration of the public transportation system that is prioritized for handling is physical integration, which has a servqual value of -1.082 with a suitability level of 73.846% and is in quadrant III of the Cartesian diagram. This can also be evidenced by the physical condition of public transportation stops and terminals in several places that are inadequate so that users still feel less comfortable and effective.